2011
DOI: 10.1111/j.1439-0523.2011.01877.x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between heterosis and genetic distances based on RAPD and AFLP markers in carrot

Abstract: The aim of this study was to estimate the correlation between heterosis in carrot hybrids and the genetic distances of their parents. The experimental material consisted of 15 inbred lines and 34 hybrids. The yield traits (total and marketable yield), as well as quality characters (carotenes, dry matter, total sugar, monosaccharides and nitrates), were evaluated. Heterosis was computed using two measurements of mid-and high-parent heterosis. Genetic distances among lines were calculated using the RAPD and AFLP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
(22 reference statements)
3
19
0
Order By: Relevance
“…Our results are in agreement with the findings of Wegary et al [83], who reported significant correlation of GD with heterosis for grain yield, plant height and ear height, similary of morphological distance with heterosis for certain traits in quality protein maize. The results obtained are also in line with the findings of Jagosz [36], who reported significant association of GD (based on RAP and AFLP markers) with heterosis for total and marketable yield in carrot. On the other hand, Tian et al [78] and Su et al [73] reported no significant correlation of PD and GD with MPH and BPH for any traits in rapeseed, chrysanthemum, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are in agreement with the findings of Wegary et al [83], who reported significant correlation of GD with heterosis for grain yield, plant height and ear height, similary of morphological distance with heterosis for certain traits in quality protein maize. The results obtained are also in line with the findings of Jagosz [36], who reported significant association of GD (based on RAP and AFLP markers) with heterosis for total and marketable yield in carrot. On the other hand, Tian et al [78] and Su et al [73] reported no significant correlation of PD and GD with MPH and BPH for any traits in rapeseed, chrysanthemum, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…Significant correlation between genetic distances (RAPD and AFLP) among inbred lines and heterosis by yield was shown in 34 hybrid combinations of carrot. However, no correlation between genetic distances and qualitative characteristics of carrot was found (Jagosz, 2011). A possibility to use genetic distances between parental lines to predict heterosis in F 1 hybrids of wheat was demonstrated as well (Krystkowiak et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…Moll et al 1965;Willi & Van Buskirk 2005), others found performance to increase with distance (e.g. Moran et al 1995;Xiao et al 1996;Amos et al 2001;Gonzalez et al 2007;Jagosz 2011), decrease with distance (e.g. McClelland & Naish 2007;Pekkala et al 2012), or no effect of genetic distance was observed at all (e.g.…”
Section: Introductionmentioning
confidence: 99%